IMPLEMENTASI PENUGASAN DOSEN DI SEKOLAH UNTUK PENGUATAN PENDIDIKAN KARAKTER PADA MATA PELAJARAN SEJARAH INDONESIA DI SMA 1 GOWA - Bahri, Bahri; Nuraeni, Nuraeni; Misnah, Misnah; Riang tati, Andi Dewi; Nurlela, Nurlela (Universitas Negeri Yogyakarta, 2022)
Integrating character education in the learning process is an effort to instill character values in students that lead to learning that not only pays attention to cognitive but also affective and psychomotor aspects. Historical subjects have an important role in character formation in students so that the values implicit in an event become very important to be integrated in learning. The implementation of character education has not yet been realized in the subjects of Indonesian history in SMA Negeri 1 Gowa because the learning models and methods used are not varied, other than that the learning tools used do not contain the character values that will be achieved at each step of learning. This leads to the inability of students to identify character values in learning history. The approach used is qualitative. While the data collection techniques used include observation, interviews and documentation. The results showed that the implementation of character education by preparing learning tools based on character education can realize character learners and be able to identify character values in historical learning material.Keywords: PDS, Character Education, Indonesian History.